2014
DOI: 10.1016/j.spinee.2014.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Reducing radiation exposure in early-onset scoliosis surgery patients: novel use of ultrasonography to measure lengthening in magnetically-controlled growing rods

Abstract: This is the first study to report the use of a novel technique using noninvasive, nonionizing ultrasound to reliably document rod distractions in EOS patients. A high level of inter- and intrarater reliabilities were noted. More importantly, the use of ultrasonography may result in fewer whole spine radiographs from being taken in patients who have had MCGRs implanted for EOS; thereby decreasing their exposure to ionizing radiation and the potential risk of future radiation-induced diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 36 publications
1
39
0
2
Order By: Relevance
“…A recent clinical study suggests that patients previously treated with the traditional growing rods can be converted to MCGRs with comparable positive results [12]. Clinical cases reporting pin fracture and failure to distract have been published over the last 2 years [11][12][13][14][15]; this is the first retrieval paper using state-of-the-art forensic analysis to determine the mechanism leading to pin fracture. We examined nine retrieved MCGRs and found that a third of them had a fractured pin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent clinical study suggests that patients previously treated with the traditional growing rods can be converted to MCGRs with comparable positive results [12]. Clinical cases reporting pin fracture and failure to distract have been published over the last 2 years [11][12][13][14][15]; this is the first retrieval paper using state-of-the-art forensic analysis to determine the mechanism leading to pin fracture. We examined nine retrieved MCGRs and found that a third of them had a fractured pin.…”
Section: Discussionmentioning
confidence: 99%
“…The lengthening procedure lasts approximately 40 s per rod and the total length is measured using a plain radiograph [8]. Recent studies have also investigated the reliability of other imaging modalities, including ultrasound [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, loosening of anchor points, ploughing of screws or rod fractures can only be detected on radiographs. Recently published results showing equivalent measurements with ultrasound and radiographs [27,28]. In our institution we have gained ample experience with ultrasound but have not established it as a routine to substitute radiography.…”
Section: Discussionmentioning
confidence: 99%
“…This concern was addressed by using outpatient ultrasound to document distraction. [15] More widespread adoption of MCGRs has now led to clinical scenarios where magnetic resonance imaging (MRI) would be a useful investigation in patients who have MCGRs implanted such as patients with known conditions including neurofibromatosis where neural symptoms subsequently occur. Indeed there have been circumstances where MCGRs have not been implanted due to concerns over safety of future MRI.…”
Section: Introductionmentioning
confidence: 99%
“…[16] MCGRs contain a rare earth magnet, therefore the manufacturer advises that the device is not compatible with MRI. [15] Theoretical concerns include: deactivation of the MCGR magnet preventing subsequent lengthening, lengthening, shortening or dislodgement of the device due to the torque resulting from the internal ferromagnetic material when a patient moves within the MRI magnetic field, or excessive heating due to eddy currents generated by the radiofrequency fields associated with MRI, leading to tissue damage. The implications of these potential effects range from the need to exchange the implant, with significant associated costs, to actual harm to the patient, which could include neural damage.…”
Section: Introductionmentioning
confidence: 99%